The Combination Effect of Simvastatin and Virgin Coconut Oil on Total Cholesterol Levels in Dislipidemic Male Albino Rats (Rattus norvegicus) - Lutfi Dewanda Nugroho; Soebagijo Adi Soelistijo; Jusak Nugraha (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2021)
Introduction: Simvastatin is a primary pharmacological therapy for dyslipidemia (hypercholesterolemia). Virgin coconut oil (VCO) is a companion intake of statin drugs considered capable of lowering blood cholesterol levels. This study aimed to determine the combination effect of statin drug groups with VCO on total cholesterol.Methods: The stages of this study started with the adaptation process of animals, giving a high-fat diet (HFD), and treatment with simvastatin and VCO. The adaptation process was conducted where the experimental animals were fed pellets and drank clean water in a container. A HFD was given by mixing pork brains with distilled water with a ratio of 1:3 as much as 2 ml per day for 21 days. In simvastatin and VCO treatment for 7 days, the experimental animals were divided into 4 groups; group I was given aquades, group II was given VCO, group III was given simvastatin, and group IV was given simvastatin and VCO. The total cholesterol levels in the blood of albino rats were examined by employing a BS-300 Chemistry Analyzer through a spectrophotometric method. The total cholesterol levels data obtained were then examined for normality (Shapiro-Wilk test) and analyzed parametrically by utilizing One-way ANOVA.Results: The average total cholesterol level in the negative control group (being given a standard diet) was 45.57 mg/dL. The averages of blood total cholesterol levels were 47.28 mg/dL, 45.00 mg/dL, 46.85 mg/dL, 41.42 mg/dL, and 44.28 mg/dL in the positive control group (given an HFD), in the treatment group I, in the treatment group II, in the treatment group III, and in the treatment group IV, respectively. There were no significant distinctions in the statistical test on decreasing blood total cholesterol among the negative control group, positive controls I, II, III, and IV.Conclusion: Combination of simvastatin and VCO tends to reduce the total cholesterol level in albino rats. This is better than just giving VCO simvastatin alone.